Efficacy Testing of H56 cDNA Tattoo Immunization against Tuberculosis in a Mouse Model - Platteel, Anouk C. M.; Nieuwenhuizen, Natalie E.; Domaszewska, Teresa; Schürer, Stefanie; Zedler, Ulrike; Brinkmann, Volker; Sijts, Alice J. A. M.; Kaufmann, Stefan H. E. (Frontiers in Immunology, 2017)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a global threat. The only approved vaccine against TB, Mycobacterium bovis bacillus Calmette-Guérin (BCG), provides insufficient protection and, being a live vaccine, can cause disseminated disease in immunocom-promised individuals. Previously we found that intradermal cDNA tattoo immunization with cDNA of tetanus toxoid fragment C domain 1 fused to cDNA of the fusion protein H56, com-prising the Mtb antigens Ag85B, ESAT-6 and Rv2660c, induced antigen-specific CD8+ T cell responses in vivo. As cDNA tattoo immunization would be safer than a live vaccine in immuno-compromised patients, we tested the protective efficacy of intradermal tattoo immunization against TB with H56 cDNA, as well as with H56_E, a construct optimized for epitope processing in a mouse model. As Mtb antigens can be used in combination with BCG to boost immune re-sponses, we also tested the protective efficacy of heterologous prime-boost, using dermal tattoo immunization with H56_E cDNA to boost BCG immunization in mice. Dermal H56 and H56_E cDNA immunization induced H56-specific CD4+ and CD8+ T cell responses and Ag85B-specific IgG antibodies, but did not reduce bacterial loads, although immunization with H56_E amelio-rated lung pathology. Both subcutaneous and intradermal immunization with BCG resulted in broad cellular immune responses, with increased frequencies of CD4+ T effector memory cells, T follicular helper cells and germinal center B cells, and resulted in reduced bacterial loads and lung pathology. Heterologous vaccination with BCG/H56_E cDNA induced increased H56-specific CD4+ and CD8+ T cell cytokine responses compared to vaccination with BCG alone, and lung pathology was significantly decreased in BCG/H56_E cDNA immunized mice compared to un-vaccinated controls. However, bacterial loads were not decreased after heterologous vaccination compared to BCG alone. CD4+ T cells responding to Ag85B- and ESAT-6-derived epitopes were predominantly IFN-+TNF-+ and TNF-+IL-2+, respectively. In conclusion, despite induc-ing appreciable immune responses to Ag85B and ESAT-6, intradermal H56 cDNA tattoo immun-ization did not substantially enhance the protective effect of BCG under